Family support and community respect for community health workers and the association of these with CHW productivity and clinic health care utilization - Nabamallika Dehingia; Holly Shakya; Dharmendra Chandurkar; Katherine Hay; Arnab Dey; Kultar Singh; Jay G Silverman; Anita Raj (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background This paper examines associations between family support and community respect as perceived by community health workers, and their productivity and maternal health care utilization in India. # Methods We conducted cross-sectional surveys with the community health workers, known as accredited social health activists (ASHA) and her clients, women with a child aged one year or less. The data were matched and merged for dyadic analysis. ASHA productivity was defined as number of households visited, number of women accompanied to a health facility, and earnings as reported by ASHAs. It also included two variables reported by the clients - number of ASHA visits during the clients' pregnancy and ASHA visits during postnatal period. Maternal health care utilization included client reports of 4+ antenatal care visits and facility delivery. Husband/family support in domestic work referred to sharing of household responsibilities. Support in ASHA-related work included help in reaching target households, help in taking clients to facilities, help in organizing village health and nutrition days, and help in filling out required paperwork. We used bivariate, multivariate, and hierarchical logistic regression models to test the associations. # Results Husband/family support in domestic work was associated with a significantly higher number of households reached by ASHAs (regression coefficient, beta (β)=0.21, P<0.001), higher number of clients accompanied to a facility for delivery (β=0.14, P=0.04), higher odds of a client receiving an ASHA visit during pregnancy (adjusted odds ratio AOR: 1.20; 95% confidence interval (CI)=1.04-1.37), and receiving 4+ antenatal care (adjusted odds ratio (AOR)=1.20, 95% CI= 1.00-1.43). Husband/family support for ASHA-related work (eg, taking on domestic labor) was also associated with a significantly higher number of households reached by ASHAs (β=0.32, P<0.001), but no significant associations were observed for health care utilization with respect to antenatal care or facility delivery. Male community members' respect for ASHAs was associated with a significantly higher number of households reached by ASHAs (β=0.36, P=0.02), and earnings (β=0.23, P=0.04). # Conclusions The study indicates the need for family support and community respect in improving ASHAs' productivity as well as health outcomes within the community they serve. Findings also suggest the need for more equitable distribution of domestic labour.